2015
DOI: 10.1111/jan.12608
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic play intervention on children's perioperative anxiety, negative emotional manifestation and postoperative pain: a randomized controlled trial

Abstract: Therapeutic play intervention is effective in reducing negative emotional manifestations before anaesthesia induction and in reducing postoperative pain in children undergoing inpatient elective surgery. These results suggest that it is useful to give children with therapeutic play intervention prior to inpatient elective surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 40 publications
5
65
0
13
Order By: Relevance
“…23 He et al suggested that therapeutic play intervention helps to reduce perioperative anxiety, negative emotional manifestations, and postoperative pain. 9 In this study, the children in the experimental group were found to be less anxious than those in the control group. The additional information provided to the mothers in the experimental group probably encouraged them to soothe their children, thereby reducing their anxiety.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…23 He et al suggested that therapeutic play intervention helps to reduce perioperative anxiety, negative emotional manifestations, and postoperative pain. 9 In this study, the children in the experimental group were found to be less anxious than those in the control group. The additional information provided to the mothers in the experimental group probably encouraged them to soothe their children, thereby reducing their anxiety.…”
Section: Discussionmentioning
confidence: 93%
“…7 However, not all parents have the competency to adequately manage their children's postoperative treatment and control any side effects. [8][9][10] Lack of postoperative management competency can adversely affect a child's care and may even cause complications. 1,11 Previous studies on pediatric tonsillectomy have suggested that parents, who have been taught pain assessment and management strategies, are better able to manage their children's pain.…”
Section: Introductionmentioning
confidence: 99%
“…, Banchs & Lerman , He et al . ). Thus, relieving preoperative anxiety is an important goal for paediatric staff.…”
Section: Introductionmentioning
confidence: 97%
“…Five studies investigated the effectiveness of therapeutic play in particular (Li et al. 2007, Vaezzadeh et al., ; Sabaq & El‐Awady, ; He, Zhu, Chan, Liam, et al., ; Dai et al., ). The core elements of this intervention included three facets: demonstration of the anaesthesia induction process by employing a doll or manikin similar to the child's age; then, children were encouraged to imitate the process afterwards under the supervision of the investigator or other qualified professionals; finally, questions and concerns raised during the process would be answered (He, Zhu, Chan, Liam, et al., ; Li et al., ).…”
Section: Resultsmentioning
confidence: 99%